Evaluation of adherence and tolerability of prolonged-release tacrolimus (Advagraf™) in kidney transplant patients in Germany: a multicenter, noninterventional study - Lehner, Lukas Johannes; Krämer, Bernhard (Clinical transplantation, 2018)
This study assessed adherence to prolonged-release tacrolimus (PR-T)-based immunosuppression during routine maintenance of renal transplant recipients in Germany. Patients had received PR-T for ≥1 month at inclusion. Data were collected during four visits (V): baseline (V1), 6 (V2), 12 (V3), and 18 (V4) months. Composite primary endpoint: nonadherence at V4, defined as self-reported nonadherence on the Basel Assessment of Adherence with Immunosuppressive Medication Scale (BAASIS©), investigator-rated nonadherence, and/or V4 tacrolimus trough level outside a predefined range. Secondary endpoints: individual BAASIS items, incidence of rejection, kidney function, and safety. Overall, 153 adult kidney recipients (mean [standard deviation] time post-transplant 5.8 [4.6] years) were included. Nonadherence was high at V4 (67.7% [95% confidence interval 58.9%, 75.6%]). Medication-taking adherence was 86.9% and 91.3% at V1 and V4, respectively; adherence to timing of medication intake was 58.2% and 58.3%, with little evidence of missed doses/drug holidays. Investigators rated adherence “good” in 85.6% of patients (V4). Two (1.3%) patients had acute rejection episodes. Kidney function remained stable (mean creatinine clearance, V1: 62.1 mL/min; V4: 65.3 mL/min). Investigators rated effectiveness of PR-T as “very good”/“good” in 91.5% of patients. Most patients (94.7%) found PR-T dosing more convenient than immediate-release tacrolimus. PR-T was well tolerated with high medication persistence.
Gesehen am 13.09.2019
First published: 20 October 2017